Automated fabrication of photopatterned gelatin hydrogels for organ-on-chips applications. (17th January 2018) - Nawroth, Janna C; Scudder, Lisa L; Halvorson, Ryan T; Tresback, Jason; Ferrier, John P; Sheehy, Sean P; Cho, Alex; Kannan, Suraj; Sunyovszki, Ilona; Goss, Josue A; Campbell, Patrick H; Parker, Kevin Kit
Abstract: Organ-on-chip platforms aim to improve preclinical models for organ-level responses to novel drug compounds. Heart-on-a-chip assays in particular require tissue engineering techniques that rely on labor-intensive photolithographic fabrication or resolution-limited 3D printing of micropatterned substrates, which limits turnover and flexibility of prototyping. We present a rapid and automated method for large scale on-demand micropatterning of gelatin hydrogels for organ-on-chip applications using a novel biocompatible laser-etching approach. Fast and automated micropatterning is achieved via photosensitization of gelatin using riboflavin-5′phosphate followed by UV laser-mediated photoablation of the gel surface in user-defined patterns only limited by the resolution of the 15 μ m wide laser focal point. Using this photopatterning approach, we generated microscale surface groove and pillar structures with feature dimensions on the order of 10–30 μ m. The standard deviation of feature height was 0.3 μ m, demonstrating robustness and reproducibility. Importantly, the UV-patterning process is non-destructive and does not alter gelatin micromechanical properties. Furthermore, as a quality control step, UV-patterned heart chip substrates were seeded with rat or human cardiac myocytes, and we verified that the resulting cardiac tissues achieved structural organization, contractile function, and long-term viability comparable to manually patterned gelatin substrates. Start-to-finish, UV-patterning shortened the time required to design and manufacture micropatterned gelatin substrates for heart-on-chip applications by up to 60% compared to traditional lithography-based approaches, providing an important technological advance enroute to automated and continuous manufacturing of organ-on-chips.